Size matters: Lower body weight pigs have a different response to immune challenge and amino acids supplementation above the estimated requirement compared to heavy pigs - Da Cunha Valini, Graziela Alves [UNESP]; Méthot, Steve; Pomar, Candido; Hauschild, Luciano [UNESP]; Remus, Aline (Oxford University Press (OUP), 2024)
The immune response varies between pigs, as not all pigs have the same response to a stressor. This variation may exist between individuals due to body weight (BW) or body composition, which may impact the capacity for coping with an immune challenge (IC). Tryptophan (Trp), threonine (Thr), and methionine (Met) requirements might also play a considerable part in supporting immune system activation while reducing variation between pigs; however, the latter has yet to be reported. This exploratory study investigated the effect of initial BW (light vs. heavy-weight) and supplementation of Trp, Thr, and Met above National Research Council (NRC) requirements on feeding behavior and the coping capacity of growing pigs under an IC. Eighty gilts were categorized into 2 groups according to BW: light-weight (LW, 22.5 kg) and heavy-weight pigs (HW, 28.5 kg). Both BW groups were group-housed for a 28-d trial in a good or poor sanitary condition (SC). Pigs within a poor SC were orally inoculated with 2 × 109 colony units of Salmonella Typhimurium, and fresh manure from a pig farm was spread on the floor. Pigs within good SC were not inoculated, nor was manure spread. Two diets were provided within each SC: control (CN) or supplemented (AA+) with Trp, Thr, and Met at 120% of NRC recommended levels. A principal component analysis was performed in R, and a feeding behavior index was calculated in SAS. Results showed that LW and HW pigs were clustered separately on day 0, where LW pigs had a positive correlation with body lipid percentage (r = 0.83), and HW pigs had a positive correlation with body protein percentage (r = 0.75). After the IC, the cluster configuration changed, with diets influencing LW more than HW pigs within poor SC. On day 14, LW fed AA + diet in poor SC was clustered separately from LW pigs fed CN diet, whereas LW fed AA + and CN diets in good SC were clustered together. For feeding behavior, in both analyzed periods (period 1: days 7 to 14; period 2: days 21 to 28), LW had lower total feed intake and shorter meals than HW pigs (P < 0.10), independent of the SC. Furthermore, LW pigs fed AA + diet had a more regular feed intake pattern than those fed CN diet, while a more irregular pattern was observed for HW pigs fed AA + diet than CN diet at period 2. These findings suggest that supplementing Trp, Thr, and Met above requirements may be a nutritional strategy for LW pigs under IC by improving feed intake regularity and reducing the probability of being susceptible to IC.
Keywords: feeding behavior; methionine; salmonella; threonine; tryptophan